The Study of the Effect of Two-Sided Variable Trends on the Occurrence of Hypertension - Marniati Marniati; Teuku Muliadi; Itza Mulyani; Enda Silvia Putri; Khairunnas Khairunnas (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2021)
Hypertension is an excessively raised blood pressure condition that can cause serious health complications and increase the risk of heart disease, stroke, and sometimes death. The problem with hypertension cases has experienced a significant fluctuation from 2014 as many as 95 cases, increasing in 2015 to 105 cases. The survey results show that hypertension that occurs in the community is caused by family history and does not pay attention to the type of food eaten. Hypertension in the community at the Meureubo Community Health Center, Meureubo District, West Aceh Regency. This study was an analytical survey with a cross-sectional design which was conducted in December 2016 with a sample of 51 people, analyzed using univariate and bivariate, then tested with chi-square. The results showed that there was an effect of genetics and lifestyle on the incidence of hypertension as evidenced by the value of P. value <α = 0.05. For the PUSKESMAS to increase motivation in the community by suggesting consuming healthy foods, exercising regularly, to achieve the expected healthy life.